The Efficacy of Ketogenic Diet for Specific Genetic Mutation in Developmental and Epileptic Encephalopathy - Ko, Ara; Jung, Da E.; Kim, Se H.; Kang, Hoon-Chul; Lee, Joon S.; Lee, Seung T.; Choi, Jong R.; Kim, Heung D. (Frontiers in Neurology, 2018)
Objectives: Pathogenic mutations in developmental and epileptic encephalopathy (DEE) are increasingly being discovered. However, little has been known about effective targeted treatments for this rare disorder. Here, we assessed the efficacy of ketogenic diet (KD) according to the genes responsible for DEE. Methods: We retrospectively evaluated the data from 333 patients who underwent a targeted next-generation sequencing panel for DEE, 155 of whom had tried KD. Patients showing ≥90% seizure reduction from baseline were considered responders. The KD efficacy was examined at 3, 6, and 12 months after initiation. Patients were divided into those with an identified pathogenic mutation (n = 73) and those without (n = 82). The KD efficacy in patients with each identified pathogenic mutation was compared with that in patients without identified genetic mutations. Results: The responder rate to KD in the patients with identified pathogenic mutations (n = 73) was 52.1%, 49.3%, and 43.8% at 3, 6, and 12 months after initiation, respectively. Patients with mutations in SCN1A (n = 18, responder rate = 77.8%, p = 0.001), KCNQ2 (n = 6, responder rate = 83.3%, p = 0.022), STXBP1 (n = 4, responder rate = 100.0%, p = 0.015), and SCN2A (n = 3, responder rate = 100.0%, p = 0.041) showed significantly better responses to KD than patients without identified genetic mutations. Patients with CDKL5 encephalopathy (n = 10, responder rate = 0.0%, p = 0.031) showed significantly less-favorable responses to KD. Conclusions: The responder rate to KD remained consistent after KD in DEE patients with specific pathogenic mutations. KD is effective in patients with DEE with genetic etiology, especially in patients with SCN1A, KCNQ2, STXBP1, and SCN2A mutations, but is less effective in patients with CDKL5 mutations. Therefore, identifying the causative gene can help predict the efficacy of KD in patients with DEE.